A Study of Sapardi Djoko Damono’s Alih Wahana: A Theoretical and Practical Study in Education - Nurromah, Okta Viana (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The development of information technology and media has changed the way human access and process information, including in education. Technology provides unlimited space for creative activities. Ultimately, new phenomena emerge that cannot be explained by one field of study alone. Through conceptual writing and a literary study of the book Alih Wahana by Sapardi Djoko Damono, along with supporting reference source, one can obtain the basic concept offered by Damono, the initiator of Alih Wahana (Vehicle Transfer) Study: vehicle source; supporting reference, and the process of vehicle transfer. The scope of vehicle transfer is not limited to literature and the humanities; all results of human creativity can be studied with this approach, including education. This study also bridges the gap between interrelated vehicles in different fields. Through the factors of the creator’s manifesto, the creative process, and habitat adaptation, the background of vehicle transfer can be identified